MASHLAHAH SEBAGAI TUJUAN INTI PEMBENTUKAN HUKUM ISLAM - Sulthon, Muhammad (IAI Darussalam, 2023)
Abstract All provisions of syara' law must lead to the aspect of mashlahah. There is almost no provision of Allah's law that is